Allergic reaction with angioedema after exposure to e-cigarette liquid: a case report - Maan Abdullah Albehair; Mohammed Aljumaan; Samer Kuleib (Saudi Journal of Emergency Medicine)
Background: The use of electronic cigarettes (e-cigarettes) is increasing worldwide. Allergic reactions have been reported from the metal used, and a few cases have been reported of angioedema of the lip, but none were related to the e-cigarette liquid. Case Presentation: We report a case of allergic reaction with angioedema from e-cigarette liquid, most likely histamine-mediated angioedema, in a healthy 24-year-old Saudi man, who did not have a history of any allergy or atopy. The subject presented complaining of left lower lip swelling 1 hour after smoking an e-cigarette and spilling liquid into the mouth. The case reported no shortness of breath, skin rash, or tongue swelling. On examination, vital signs were normal. The patient had left lower lip swelling and gingival erythema. The patient reported having experienced a similar episode in the past with a different type of e-cigarette liquid on the right lower lip, but it was less severe. The patient was diagnosed with allergic reaction with angioedema from the e-cigarette liquid and was managed with hydrocortisone 200 mg Intravenous and chlorphenamine 10 mg Intramuscular, and was discharged after 3 hours with full recovery. Conclusion: E-cigarettes are still relatively new and could cause harm. Further studies and reports should be conducted concerning the health effects of e-cigarettes. [SJEMed 2021; 2(3.000): 278-281]